Facing Climate Change Risk: Green Theology Commitment Crisis in Ritual Practices - Henky Fernando; Eko Ariwidodo; Qodariah Barkah; Eny Boedi Orbawati; M. Nastain; Farahdilla Kutsiyah; Yuniar Galuh Larasati (Universitas Islam Negeri Madura, 2025)
The crisis of commitment to green theology has been sublimated into collective consciousness, making the potential ecological damage caused by ritual practices often seem normal or acceptable. However, this issue tends to be overlooked in academic discussions. This study adopts a qualitative descriptive approach using a case study method. Data collection and analysis were conducted intensively by examining online news articles published between May 29 and June 11, 2025, using the keywords “climate change, ritual, and ecological knowledge” via the Google search engine. The findings indicate that ritual practices conducted in natural settings frequently disregard their long-term ecological implications. This situation is further exacerbated by the use of non-environmentally friendly ritual materials, such as plastic and synthetic substances, which leave residues that are not easily biodegradable. The lack of waste management and the absence of ecological rehabilitation efforts following the rituals reflect a weak commitment to green theology in the implementation of tradition-based rituals. The significance of this study lies in its emphasis on the need to reorient traditional ritual practices so that they are theologically and ecologically integrated, thereby supporting environmental preservation without compromising religious intentions and cultural values.